Flexible Three‐Dimensional Graphene Hydrogels with Superior Conductivity and Excellent Electrochemical Performance for Supercapacitor Electrodes. Issue 10 (3rd July 2017) - Zhang, Juan; Zhou, Bo; Zhao, Bo; Si, Ling; Jiang, Xiaoqing
Abstract : Three‐dimensional porous graphene hydrogels have been prepared by a green and facile but very efficient approach using glucose as an assistant. Based on a one‐step hydrothermal reaction with optimal experimental conditions such as the reaction time and temperature, the graphene hydrogels exhibit a superior electrical conductivity (95.3 S/m) and can be used as supercapacitor electrode without any binder or conducting additives but showing a high specific capacitance of 384.6 F/g at a current density of 1 A/g. The results show that addition of glucose can not only greatly decrease the reaction temperature but also shorten the reaction time. The superior performance of the three‐dimensional porous graphene hydrogels as electrode for supercapacitor suggests its promising potentials in the field of energy storage devices. Abstract : Flexible three‐dimensional graphene hydrogels (GHs‐Glu) have been prepared via a one‐step hydrothermal reaction and shown an excellent electrochemical performance for supercapacitor electrode.